Search for dark matter from the center of the Earth with 10 years of IceCube data - IceCube data collaboration (European Physical Journal C: Particles and Fields)
Abstract The nature of dark matter remains unresolved in fundamental physics. Weakly Interacting Massive Particles (WIMPs), which could explain the nature of dark matter, can be captured by celestial bodies like the Sun or Earth, leading to enhanced self-annihilation into Standard Model particles including neutrinos detectable by neutrino telescopes such as the IceCube Neutrino Observatory. This article presents a search for muon neutrinos from the center of the Earth performed with 10 years of IceCube data using a track-like event selection. We considered a number of WIMP annihilation channels ( $$χ χ → τ ^+τ ^-$$ χ χ → τ + τ - / $$W^+W^-$$ W + W - / $$b\bar{b}$$ b b ¯ ) and masses ranging from 10 GeV to 10 TeV. No significant excess over background due to a dark matter signal was found while the most significant result corresponds to the annihilation channel $$χ χ → b\bar{b}$$ χ χ → b b ¯ for the mass $$m_{χ }=250$$ m χ = 250 GeV with a post-trial significance of $$1.06σ $$ 1.06 σ . Our results are competitive with previous such searches and direct detection experiments. Our upper limits on the spin-independent WIMP scattering are world-leading among neutrino telescopes for WIMP masses $$m_{χ }>100$$ m χ > 100 GeV.